Fiscal Policy and Private Sector Saving Behavior : Tests of Ricardian Equivalence in Some Developing Economies. (IMF Working Papers; Working Paper ;, 1987)
Tax or debt financing of a given rate of government expenditures would, according to the now well-known Ricardian Equivalence proposition, have equivalent effects on aggregate demand. Among the reasons for a deviation from the equivalence is the possibility that the government and the private sector have different planning horizons. The paper finds no empirical support for differing planning horizons across sectors in a group of 16 developing economies and, therefore, provides empirical evidence for the equivalence hypothesis.